Strength and conditioning for combat sports athletes (Revista de Artes Marciales Asiáticas, 2021)
Editors• Emerson Franchini – University of São Paulo, São Paulo (Brazil)• Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile) Authors• Ursula Ferreira Julio – University of São Paulo, São Paulo (Brazil)• Emerson Franchini – University of São Paulo, São Paulo (Brazil)• Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile)• João Paulo Lopes-Silva – CESMAC University Centre (Brazil)• Braulio Henrique Magnani Branco – Cesumar University (Brazil)• Jonatas Ferreira da Silva Santos – Federal University of the Jequitinhonha and Mucuri Valleys (Brazil)• Rubens Santos-Junior – State University of Pará (Brazil) Reviewers• Filipa Almeida – Universidad de Granada (Spain)• Juan Bonitch Góngora – Universidad de Granada (Spain)• Eduardo Carballeira Fernández – Universidade da Coruña (Spain)• Daniele Detanico – Universidade Federal de Santa Catarina (Brazil)• Raquel Escobar Molina – Universidad de Granada (Spain)• Matheus Hausen – Brazil Olympic Committee (Brazil)• Raquel Hernandez García – Universidad de Murcia (Spain)• Eliseo Iglesias Soler – Universidade da Coruña (Spain)• Carlos Montero Carretero – Universidad Miguel Hernández (Spain)• Emanuela Pierantozzi – Università degli Studi di Genova (Italy)• Luis Santos Rodríguez – Universidad de León (Spain)• Jozef Simenko – University of Essex (UK)